Development of a trauma-informed substance use and sexual risk reduction intervention for young South African women - Myers-Franchi, Bronwyn; Carney, T.; Browne, F.A.; Wechsberg, W.M. (DOVE MEDICAL PRESS LTD, 2018)
Purpose: To develop a trauma-informed substance use and sexual risk reduction intervention for young South African women at risk of HIV.